2013
DOI: 10.12693/aphyspola.123.673
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of KP-HSA Complex by Spectroscopic Methods

Abstract: The main objective of the presented study was to characterize the high (HAS) and low anity (LAS) binding sites of ketoprofen (KP) in human serum albumin (HSA) structure with the use of spectrouorescence and proton nuclear magnetic resonance spectroscopy. In vitro uorescence analysis was used to estimate the eect of KP on the HSA uorescence. The association constants Ka [M −1 ] of KP-HSA complex in the HAS were determined with the use of Scatchard, Klotz, and Hill analysis. The quenching KQ [M −1 ] constants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…These curves show negative deviation from linearity, mainly in the higher concentration range of indomethacin, and concave towards the x-axis. This phenomenon usually happens when there is more than one tryptophan residue with a distinct environment and different accessibility to the quencher [ 45 , 49 , 50 ], but it is well known that HSA has only one tryptophan residue located in the subdomain IIA, thus, there is a possibility of the existence of more than one binding site for indomethacin inside HSA [ 51 ], and the larger distance of secondary binding site in comparison to the primary one reduced the quenching efficiency, thus, a negative deviation in the Stern–Volmer plots could be expected [ 52 , 53 , 54 ]. Silva and coworkers have suggested that the binding of a ligand to the HSA may lead to the possible conformational change followed by the exposition of lower affinity binding sites [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…These curves show negative deviation from linearity, mainly in the higher concentration range of indomethacin, and concave towards the x-axis. This phenomenon usually happens when there is more than one tryptophan residue with a distinct environment and different accessibility to the quencher [ 45 , 49 , 50 ], but it is well known that HSA has only one tryptophan residue located in the subdomain IIA, thus, there is a possibility of the existence of more than one binding site for indomethacin inside HSA [ 51 ], and the larger distance of secondary binding site in comparison to the primary one reduced the quenching efficiency, thus, a negative deviation in the Stern–Volmer plots could be expected [ 52 , 53 , 54 ]. Silva and coworkers have suggested that the binding of a ligand to the HSA may lead to the possible conformational change followed by the exposition of lower affinity binding sites [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…It points to the dynamic mechanism of quenching. At higher concentrations, positive deviation from linearity suggests a more complex quenching process, probably an additional presence of a static component in the quenching mechanism [ 60 , 61 ]. From the linear part of a regression, F 0 /F versus [c] the K SV constant 2 × 10 4 M −1 was calculated.…”
Section: Resultsmentioning
confidence: 99%
“…ANS is an extrinsic fluorescent probe with low fluorescent quantum yield in water, but it becomes much brighter in nonpolar solvents or after adsorption onto proteins with exposed hydrophobic portions . ANS can be used to study the binding properties of hydrophobic molecules onto protein because the fluorescence of ANS provides information on all of the hydrophobic binding sites of HSA . Changes in PSH monitored by ANS can be calculated by the following equation : PSH =Fmax[ HSA ]Kd app where F max is the maximum fluorescence intensity at the saturated ANS concentration, which indicates the number of surface hydrophobic sites of HSA.…”
Section: Resultsmentioning
confidence: 99%
“…Kd app is the apparent dissociation constant of ANS to HSA, and 1/Kd app is the binding affinity of the ANS–HSA complex . F max and 1/Kd app can be calculated by the Scatchard equation : F[ ANS ]free=FKd app +FmaxKdappwhere [ANS] free is the concentration of free ANS and can be obtained from the difference between the total and bound concentration of ANS as follows : The concentration of bound ANS can be calculated by the following equation : [ ANS ] bound =FB B can be obtained using the method of Cardamone and Puri , which assumed that a linear relationship exists between fluorescence intensity ( F ) and ANS concentration (c) ( F = B c ) in very dilute solutions of ANS (0–2.0 μM).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation